Achieving Excellence in Stakeholder Management - Scharioth, Joachim; Huber, Margit (Springer Berlin Heidelberg, 2003)
Today, Stakeholder Management is a term commonly used to describe the policy towards all interest groups that have a stake in a company or an institution, but the crucial question is how this concept can be best applied to a company's context. In this book, companies using a Stakeholder Management tool give their first-hand account of how this tool enables them to successfully measure, monitor and manage their stakeholders' performance. The experience of these companies highlights how across different sectors and countries strong customer relationships, committed employees and successful relationships with suppliers can be created to stay at the forefront of today's global economy. Company contributions are complemented by expert articles about current business topics such as Performance Measurement, Balanced Scorecard and Data Mining methodologies
Keywords: Management; Marketing; Beziehungsmanagement; Verbraucherzufriedenheit; Stakeholder; Qualitätsmanagement; Kundenmanagement